Entrenamiento para la Extracción y Evaluación de la Calidad Seminal del Camélido Sudamericano en el Campus Salache. - De la Cueva Madera, Juan Andrés (2019)
The investigation was carried out in order to determine which is the most effective method for the training and extraction of semen from a South American camelid, in the Cotopaxi Province, Latacunga Canton in the Technical University of Cotopaxi within the facilities of the Salache Campus, in the reproduction biotechnology laboratory of the Veterinary Medicine major with the objective of evaluating the seminal quality of the South American camelid by means of the implementation of a training method for the semen extraction that allows to determine the viability of stallion sperm in the Salache Campus. Two South American donor camelids were used: an alpaco and a llamingo, the animals were trained by isolating them and then two selected females were subjected to the clamping technique to simulate the reproduction attitude of this species, using two mannequins such as: the rump and the complete one, the sample of the ejaculation was extracted. The ejaculated was assessed, the macroscopic characteristics such as volume, color, pH, smell and microscopic characteristics such as: individual motility, mass motility, morphology, morph abnormalities with the neubouel camera, microscope and the spermatic characters were evaluated after obtaining the fresh ejaculated using the Triladyl® thinner. A descriptive design was made for the statistical analysis, the values were handled as the maximum, minimum and average range. The data were analyzed in tables and through the Excel program, statistical analysis was performed to achieve the above-mentioned values. After the investigation it was possible to determine that the animals show no interest of acceptance when the complete mannequin method is used, however after a short training period the animals facilitate the training when the rump mannequin is used with the presence of the female in subjection, showing that when using this technique the macroscopic and microscopic visibility parameters related to the seminal quality improved remarkably as the animal becomes trained and as an additional data it is more feasible not to use the diluent